Historical introduction to human diversity II - Swallow, Dallas (Henry Stewart Talks, 2009)
Electrophoresis, Electrophoretic mobility, Amino acids, Specific detection methods, Detecting protein size differences, Ioselectric focusing, Protein polymorphism, DNA polymorphism and electrophoresis, Tandem repeats, Genotype and phenotype, Epistasis, Isozymes, Many proteins are encoded by multiple genes, Multimeric proteins, How do we know that a protein is encoded by multiple genes/alleles?, HapMap, Functional implications of genetic variation